Multidrug-Resistant Uropathogens, An Emerging Threat: Observational Study in a Tertiary Care Hospital of Azad Kashmir - Zeb, Muhammad Aurang; Nadeem, Muhammad; Tariq, Tufail Hussain; Siddiq, Shazia; Zaib, Jahangir; Mahmood, Muhammad Arif; Akbar, Adiba (Pakistan Armed Forces Medical Journal, 2022)
Objective: To detect the resistant pattern of uropathogens and find the association of different factors with the resistance in the Poonch District of Azad Kashmir. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Medicine, Shaikh Khalifa Bin Zayed Hospital, Rawalakot, from Mar to Aug 2019. Methodology: Patients having signs and symptoms of urinary tract infection and growth of bacteria on urine culture were included in the study. The antimicrobial susceptibility of the isolates was determined by using the standard, modified Kirby Buer disc diffusion method. Zone sizes were interpreted following Clinical Laboratory Standards Institute (CLSI) 2019 guidelines. Results: 68 culture-positive patients were included in the study, 45 (66%) patients were female. There was a previous history of urinary tract infection in 44 (64.7%) patients, and 52 (76.5%) gave a history of antibiotic use in the last three months. E. coli was the commonest organism isolated, followed by Klebsiella, Proteus and Pseudomonas. All patients were resistant to at least one antibiotic, 48 (72%) isolates were multi-drug resistant. Uropathogens showed the highest resistance to Ampicillin in 67 (98.5%) patients and the lowest resistance to Piperacillin/Tazobactam 2 (3%) patients only. Resistance was significantly higher in patients having a history of recurrent urinary tract infection (p=0.028) and the use of antibiotics in the last three months (p<0.001). Conclusion: Resistance to antimicrobial agents is increasing in community-acquired urinary tract infections. Resistance is significantly higher in patients having a history of recurrent urinary tract infection and the use of antibiotics in the..........